Immune-based treatment re-challenge in renal cell carcinoma: A systematic review and meta-analysis - Papathanassiou, Maria; Tamposis, Ioannis; Exarchou-Kouveli, Kalliopi K.; Kontou, Panagiota I.; de Paz, Anna Tzortzi; Mitrakas, Lampros; Samara, Maria; Bagos, Pantelis G.; Tzortzis, Vassilios; Vlachostergios, Panagiotis J. (Frontiers in Oncology, 2022)
The use of immune checkpoint inhibitors (ICIs) as a front-line treatment for metastatic renal cell carcinoma (RCC) has significantly improved patient’ outcome. However, little is known about the efficacy or lack thereof of immunotherapy after prior use of anti-PD1/PD-L1 or/and anti-CTLA monoclonal antibodies. Electronic databases, including PubMed, EMBASE, Medline, Web of Science, and Cochrane Library, were comprehensively searched from inception to July 2022. Objective response rates (ORR), progression-free survival (PFS), and ≥ grade 3 adverse events (AEs) were assessed in the meta-analysis, along with corresponding 95% confidence intervals (CIs) and publication bias. Ten studies which contained a total of 500 patients were included. The pooled ORR was 19% (95% CI: 10, 31), and PFS was 5.6 months (95% CI: 4.1, 7.8). There were ≥ grade 3 AEs noted in 25% of patients (95% CI: 14, 37). This meta-analysis on different second-line ICI-containing therapies in ICI-pretreated mRCC patients supports a modest efficacy and tolerable toxicity.